Association between pan-immune-inflammation value and Serum Klotho levels: a cross-sectional analysis of renal function mediation - Liu, Mingjie; Zhou, Xuan; Xu, Han; Wang, Yan; Duan, Yuting; Guo, Xiangru; Wei, Bai (Frontiers in Immunology, 2025)
IntroductionKlotho has emerged as a promising biomarker of aging processes. Although inflammation is known to modulate Klotho expression, the relationship between Pan-Immune-Inflammation Value (PIV) and serum Klotho levels has not been investigated. This study aimed to examine the association between PIV and serum Klotho levels while exploring the potential mediating effects of renal function parameters.MethodsA cross-sectional analysis was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 2007-2016. A total of 13,406 participants were included. Multiple linear regression models were used to evaluate the association between PIV and Klotho levels. Boruta feature selection method was used to identify variables included in the multivariable models. Smooth curve fitting was performed to examine potential non-linear relationships and threshold effect analysis was conducted using a two-piecewise linear regression model. Mediation analysis was conducted to assess the role of renal function indicators. Stratified analyses were performed to identify potential effect modifiers.ResultsAfter fully adjusting for potential confounders, PIV showed a significant inverse association with serum Klotho levels (β=-0.11, 95%CI: -0.15, -0.07, P <0.0001). This relationship exhibited a U-shaped pattern with a threshold effect at PIV=800 (P for log-likelihood ratio = 0.003). Renal function indicators significantly mediated this association, with serum uric acid showing the strongest mediating effect (8.32%, P <0.0001), followed by estimated glomerular filtration rate (6.91%, P <0.0001), blood urea nitrogen (6.64%, P <0.0001), and serum creatinine (5.49%, P <0.0001). Cancer survivors exhibited significantly lower Klotho levels than non-cancer participants (813.74 ± 8.55 vs. 849.69 ± 5.08 pg/mL; P < 0.0001), as well as higher PIV values (320.07 ± 6.58 vs. 299.07 ± 3.44; P = 0.0059).ConclusionElevated PIV was found to be significantly associated with lower klotho levels, with renal function indicators playing a mediating role.